PROGRAM PENGEMBANGAN CURUG MUNTU SEBAGAI PENGUATAN PROGRAM EKOWISATA DI DESA KETENGER, KECAMATAN BATURRADEN, KABUPATEN BANYUMAS – PEMBERDAYAAN KEMITRAAN MASYARAKAT - Riyatno, Riyatno; Wicaksono, Agung; Runtiko, Agus Ganjar; Huda, Farhat; Abiwardhana, Muhammad Fachry (Universitas Mataram, 2025)
Curug Muntu Development Program in Ketenger Village, Baturraden District, Banyumas Regency, aims to strengthen ecotourism in the area. Curug Muntu, which is known as a natural tourist attraction, has great potential to support the local economy and increase awareness of environmental conservation. So far, Curug Muntu has not been used as an ecotourism destination in Ketenger village because its condition still needs to be managed. Its existence is different from the two waterfalls that have been managed as tourist destinations, namely Curug Jenggala and Curug Bayan. This development involves empowering local communities through partnerships, which is expected to improve infrastructure, increase tourism service capacity, and provide direct economic benefits to village residents. This program is part of a larger effort to develop tourism potential in Banyumas and promote sustainable ecotourism. Through training and practice during the community service program, the community succeeded in creating infrastructure leading to and at Curug Muntu, increasing the capacity of tourism services by creating social media to promote Curug Muntu, and opening up employment opportunities for the surrounding community. With the introduction of social media platforms such as Instagram, Facebook, and TikTok, Curug Muntu is starting to become widely known, which is marked by an increase in tourist visit.